2017
DOI: 10.1111/acer.13525
|View full text |Cite
|
Sign up to set email alerts
|

Age of Alcohol Initiation and Progression to Binge Drinking in Adolescence: A Prospective Cohort Study

Abstract: Initiating alcohol use earlier in adolescence is associated with an increased risk of binge drinking and higher quantity of consumption in late secondary school, supporting an argument for delaying alcohol initiation for as long as possible to reduce the risk for problematic use in later adolescence and the alcohol-related harms that may accompany this use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 50 publications
2
45
0
5
Order By: Relevance
“…Additionally, there was evidence of a dose-response relationship between other supply and the five primary outcomes, which is consistent with earlier age of initiation being associated with later bingeing (appendix pp 65-82). 22 Although other supply was associated with more problems than was parental supply, our study shows that there is no rationale for parents to give alcohol to adolescents younger than the legal purchase age. Parental supply only remains associated with adverse adolescent drinking outcomes, compared with no supply, and a combination of parental and other supply was not associated with lower odds of adverse outcomes than other supply only.…”
Section: Discussionmentioning
confidence: 58%
“…Additionally, there was evidence of a dose-response relationship between other supply and the five primary outcomes, which is consistent with earlier age of initiation being associated with later bingeing (appendix pp 65-82). 22 Although other supply was associated with more problems than was parental supply, our study shows that there is no rationale for parents to give alcohol to adolescents younger than the legal purchase age. Parental supply only remains associated with adverse adolescent drinking outcomes, compared with no supply, and a combination of parental and other supply was not associated with lower odds of adverse outcomes than other supply only.…”
Section: Discussionmentioning
confidence: 58%
“…Given that a solid association is a requirement for causation, our results would not lend empirical basis to a strong causal link between ED and dependence. Our findings suggest, at least at the epidemiological level, and as found in many of the few prospective studies that control for third variables (Aiken et al, 2018), that the association may be due to genetic, biologic, or psychosocial vulnerabilities that promote consumption outside cultural norms. However, since there is evidence of biological mechanisms that increase the risk of developing alcohol dependence after ED (Buchmann et al, 2009;Varlinskaya et al, 2020) and that ED may exacerbate genetic influences (Agrawal et al, 2009), an alternative possibility is that the causal link is anteceded by genetic psychosocial characteristics and also strongly moderated by them.…”
Section: Relationships Between Ed and Dependence For All Countries Ansupporting
confidence: 62%
“…Our second aim was to examine the mechanism by which sensation seeking is related to heavy alcohol use among high school seniors. Specifically, because sensation seeking is related to age of drinking initiation (Jensen et al, 2017;Malmberg et al, 2012) and age of drinking initiation is related to alcohol use and binge drinking among adolescents (Aiken et al, 2017), we hypothesized that early age of drinking initiation would provide a potential explanation for how sensation seeking is related heavy alcohol use among high school seniors. We found support for this hypothesis, as the mediational model indicated high sensation seeking was significantly associated with earlier age of initiation of drinking, which in turn, was related to higher levels of heavy alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also reported that the initiation of alcohol use in late childhood (prior to age 11) is related to an increase in chronicity of adult alcohol dependence relative to initiation during early adolescence (ages 11-14) (Guttmannova et al, 2011). More recent research adds to these findings, indicating that early initiation of alcohol use is associated with alcohol-related health and social consequences (Donoghue et al, 2017), an increased risk of alcohol use and binge drinking later in adolescence (Aiken et al, 2017) and being classified in a high risk group of college students who report multiple and repeated alcohol-related consequences (Scaglione et al, 2015). Thus, delaying alcohol initiation is important to reduce the risk of heavy drinking and alcohol-related consequences both in adolescence and into adulthood.…”
mentioning
confidence: 97%